2019
DOI: 10.1590/2317-1782/20182018184
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento e aplicação de um game sobre saúde e higiene vocal em adultos

Abstract: RESUMO Objetivo Desenvolver um game sobre saúde e higiene vocal (VoxPedia) e aplicá-lo em adultos, para investigar o conhecimento em cuidados vocais e compreender a autoavaliação vocal dos respondentes. Método Participaram 293 adultos, 204 mulheres e 129 profissionais da voz, convidados através de mídias digitais. Os participantes responderam: 1) Termo de Consentimento Livre e Esclarecido (TCLE); 2) Dados de Identificação; 3) Protocolo do Índice de Desvantagem Vocal (IDV-10); 4) Questionário de Saúde e Higie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
1
0
4
Order By: Relevance
“…Using this cutoff point, it is possible to carry out screenings to identify groups at risk for vocal changes and/or groups in which one wants to know the level of knowledge on this topic (15) . Some studies were carried out using this questionnaire, with adults in general (16) , classical and popular singers (15), pastors (17), and theater students (18) . In the study with classical and popular singers (15) , the results showed that the perception of vocal changes in these two groups seems to be unrelated to the level of knowledge and vocal hygiene.…”
Section: Introductionmentioning
confidence: 99%
“…Using this cutoff point, it is possible to carry out screenings to identify groups at risk for vocal changes and/or groups in which one wants to know the level of knowledge on this topic (15) . Some studies were carried out using this questionnaire, with adults in general (16) , classical and popular singers (15), pastors (17), and theater students (18) . In the study with classical and popular singers (15) , the results showed that the perception of vocal changes in these two groups seems to be unrelated to the level of knowledge and vocal hygiene.…”
Section: Introductionmentioning
confidence: 99%
“…Alguns estudos foram realizados a partir da aplicação desse questionário, com adultos em geral (16) , cantores eruditos e populares (15) , pastores (17) e estudantes de teatro (18) . No estudo com cantores eruditos e populares (15) , os resultados mostraram que a percepção de alteração vocal nesses dois grupos parece não ter relação com o grau de conhecimento e higiene vocal.…”
Section: Introductionunclassified
“…Apreende-se que estudos relacionados à construção e validação de jogos vêm sendo produzidos em diversos cenários da saúde, mas com escassez em relação à saúde mental. Exemplifica-se, portanto, um jogo educativo em formato de quiz que foi desenvolvido para investigar conhecimentos da população em geral sobre saúde e higiene vocal em adultos (6) . Retrata-se também o desenvolvimento de um jogo para smartphone para conscientização sobre o vírus do Papiloma Humano (HPV) como fator de risco para o câncer do colo do útero (7) .…”
Section: Introductionunclassified